Facts and Factors about Permanent Pacemakers Lead Displacement - Khan, Zahoor Ahmad; Khan, Muhammad Asghar (Journal of Postgraduate Medical Institute, 2025)
Objective: To share the authors' clinical experience with lead displacement in permanent pacemakers, identify the potential causes of this issue, and explore how these causes can be avoided to improve patient outcomes. Methodology: For all those patients who presented with a displacement of lead, a detailed history was obtained, and their permanent pacemaker's implantation procedure record was re-examined for the possible causes of lead displacement. The site of the device was explored, and the lead's integrity was checked and readjusted. If the adjustment was not possible, then the lead was extracted, and the screwing system of the lead was examined outside the patient's body, and the new lead was implanted. All the data so collected was analyzed on SPSS version 22. Results: A total of 1670 procedures were retrospectively analyzed critically. There were 47 patients with lead displacement. Atrial lead displacement was documented in 10 cases. Ventricular lead was displaced in 37 patients. All patients with ventricular lead displacement had their initial placement of lead at the right ventricle apex. 20 leads were readjusted and 20 were replaced. In 7 cases the old lead was nor extractible neither repositionable. Conclusion: Lead displacement in permanent pacemakers is one of the common complications that can best be minimized by addressing all the responsible factors for lead displacement at the time of implantation.